Jendela Hemat Energi pada Fasade Rumah Susun di Jakarta - Daryanto, Daryanto; S., Firza Utama (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Window is one of building components that is directly related to lighting and ventilation. Currently a lot of vertical housings pay less attention to the design of energy-efficient windows. This study aims to find energy efficient windows that are applicable to vertical housing. Surveys on some vertical housings in Jakarta was conducted and environmental simulation programs using CFD and Ecotect was used to explore and analyze the performance of windows for natural lighting and ventilation and further developing of energy efficient windows. The result showed that the Jalousie windows mounted on the center of wall facing out and two louvers above the entrance and upperside of walls in the opposite side of rooms, combined with openings at the bottom of doors are able to create optimum cross ventilation. The resulted wind speed within the range of 0.15 to 0.12 m/s is enough to make comfortable air flow effect, and the average natural lighting of 200 lux is adequate forresidential activity.